Pelayanan Skrining Obesitas dan Obesitas Sentral pada Populasi Lanjut Usia melalui Pengukuran Indeks Massa Tubuh Dan Lingkar Pinggang - Santoso, Alexander Halim; Kartolo, Marenra Shinery; Alifia, Tosya Putri; Kusuma, Kanaya Fide; Gunaidi, Farell Christian; Kurniawan, Junius (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
Abstract: Obesity is a global epidemic and a significant public health problem. In the elderly population, obesity is defined as a BMI ≥ 25 kg/m². In the United States, the prevalence of obesity among the elderly is 37.1% in men and 33.6% in women over the age of 60. Obesity increases the risk of chronic diseases such as type 2 diabetes, hypertension and cardiovascular disease, and can cause psychological problems such as sleep disorders and lack of self-confidence. Accurate obesity risk assessment involves measuring Body Mass Index (BMI) and waist circumference. This activity uses the Plan-Do-Check-Act (PDCA) methodology to screen for obesity in the elderly at Hana Nursing Home, South Tangerang. The screening includes anthropometric measurements of BMI and waist circumference, followed by evaluation and nutritional counseling for at-risk individuals. 9 people (14.75%) had overweight nutritional status, 3 people (4.92%) had obese nutritional status, and 35 people (57.38%) were at risk of central obesity. Routine anthropometric measurements are critical for monitoring obesity and implementing preventive measures to improve overall health outcomes, improve quality of life, and reduce obesity-related morbidity and mortality rates. Keywords: Obesity, Central Obesity, Elderly, Body Mass Index, Waist Circumference